Growth differentiation factor-15 as a biomarker for intensive care unit-acquired weakness: a meta-analysis - Wang, Bing-Han; Qi, Meng-Ying; Yang, Zheng; He, Gui-Lan; Meng, Si-Ya (Frontiers in Medicine, 2025)
BackgroundGrowth differentiation factor-15 (GDF-15) may be a potential biomarker for intensive care unit-acquired weakness (ICU-AW). In this study, we aimed to quantitative analysis the levels of GDF-15 in patients with ICU-AW and in non-ICU-AW, and then to determine its potential diagnostic utility.MethodsTwo researchers separately conducted a systematic search of the relevant studies up to May 2023 in various literature databases (PubMed, Cochrane, Web of Science, Embase, and CINAHL). Studies were selected according to the inclusion and exclusion criteria, and quality evaluation of the included studies was conducted by using QUADAS-2 provided by Review Manager 5.3. The software packages Meta Disc (C1.4) and Stata17.0 were used for the meta-analysis. The data were combined with fixed-effects model, and the summary receiver operating characteristic curve was drawn to evaluate the overall diagnostic accuracy of GDF-15.ResultsWe identified 6 eligible studies comprising 401 patients with ICU-AW. The sensitivity, specificity, diagnostic odds ratio (DOR), and area under the curve (AUC) for the discriminative performance of GDF-15 as a diagnostic biomarker were 0.82 (95% confidence interval (CI):0.78–0.86), 0.83 (95% CI: 0.61–0.88), 21.39 (95% CI: 13.36–34.24), and 0.88 (95% CI: 0.85–0.91), respectively.ConclusionGDF-15 is a candidate biomarker in diagnosing of ICU-AW from non-ICU-AW.